Javanese People's Kejawen Tradition Maqashid Sharia Perspective - Muhammad Sirojudin Sidiq; Muhammad Farid Zulkarnain; Muhamad Ibnu Afrelian; Anggita Vela (STIT Sunan Giri Bima, 2025)
This article examines the Kejawen tradition of Javanese society from the perspective of maqashid sharia. The issue raised is how the position of Kejawen tradition which is rich in cultural values and spirituality in the view of Islam, especially when analyzed through the five main principles of maqashid sharia: protecting religion, soul, mind, offspring, and property. This study aims to assess whether the values in the practice of Kejawen traditions, such as slametan, mitoni, tedhak siten, and wetonan, are in line with the basic principles of Islamic law. The method used is qualitative research with a library research approach and normative-theological analysis. This article analyzes the relationship between traditional values and the elements of benefit aimed at by sharia, as well as seeing the extent to which acculturation of local culture and Islam can occur harmoniously. The results show that Kejawen traditions such as selametan, mitoni, wetonan and tedhak siten contain moral, social and spiritual values that do not conflict with maqashid sharia, and even have the potential to support the achievement of benefits in people's lives. In conclusion, Kejawen tradition can be maintained and preserved as long as the values it contains remain in the corridor of tawhid and do not contain elements of shirk. This research implies that maqashid sharia can be an effective analytical tool to examine local culture contextually, and become a bridge between religion and culture in the lives of Indonesian Muslims.